1994
DOI: 10.1152/ajpheart.1994.267.3.h1157
|View full text |Cite
|
Sign up to set email alerts
|

Time course of postnatal changes in rat heart action potential and in transient outward current is different

Abstract: The rat ventricular action potential shortens after birth. The contribution of increases in the transient outward current (Ito) to postnatal action potential shortening was assessed by measuring Ito in isolated cells and by determining the effect of 2 mM 4-aminopyridine (4-AP) on the action potentials of papillary muscles. 4-AP had no effect on 1-day action potential duration at 25% repolarization (APD25), and 1-day cells had little Ito. In 8- to 10-day muscles, 4-AP caused a small, but significant, increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 0 publications
7
19
0
Order By: Relevance
“…Control values of resting potential and action potential durations for neonatal rat cells are consistent with those from reports using similar conditions. 21,22 Likewise, the control resting potential and action potential durations of gerbil cardiomyocytes are similar to values reported for adult rats. 21,22 …”
Section: Cardiac Action Potentialsupporting
confidence: 73%
“…Control values of resting potential and action potential durations for neonatal rat cells are consistent with those from reports using similar conditions. 21,22 Likewise, the control resting potential and action potential durations of gerbil cardiomyocytes are similar to values reported for adult rats. 21,22 …”
Section: Cardiac Action Potentialsupporting
confidence: 73%
“…increase of heart rate and ion channel expression during maturation, APs become shorter at the adult than at the embryonic, fetal or neonatal stage. The plateau phase of neonatal rat cardiomyocytes for example becomes very short or even absent in the adult heart [54]. Accordingly, we found that the plateau phase in APs of the early murine embryonic heart is significantly prolonged as compared to late embryonic and particularly adult stages (unpublished observation).…”
Section: Discussionmentioning
confidence: 55%
“…In human atrial myocytes, APD increases with age, particularly during the earliest years of life [12]. In contrast, however, newborn rat ventricular myocytes have a characteristically long AP that shortens considerably during development [22,37]. Our present findings demonstrate that, like most mammalian species except the rat, ventricular AP amplitude and duration increase after birth in the rabbit.…”
Section: Postnatal Changes In Apdmentioning
confidence: 48%